Energy absorption and toughness analysis on FSW butt joint of AA 5052 and AA 5083 - Rahadian Nopriantoko (Politeknik Negeri Lhokseumawe, 2023)
Friction Stir Welding (FSW) is an efficient and effective welding method with good-quality welds. Aluminum Alloy (AA) has been widely used for various automotive needs, including in vehicle manufacturing. AA series 5XXX is a type of material used for vehicle manufacturing because it has good strength properties even after the joining process. A similar butt joint using the FSW method was carried out on material AA 5052 and AA 5083. The results of the welding were then given radiographic testing to determine the general condition of the welds. The impact test was carried out according to the procedures standard of ASTM on the welding results to analyze the energy absorption and toughness properties of welds by getting the impact value of the welded joint, and then looking for the quantity ratio to the impact value of the base material. After that, the results and discussion were obtained that the welded areas showed different impact strength and absorbed energy value, which is compared to the base material the range is below with a decrease in value of between 34% and 68% of the initial toughness strength of the parent material. The reduction in toughness strength can be attributed to the influence of mechanical properties during the welding process. Nevertheless, the welds demonstrated good quality and integrity, highlighting FSW's efficacy in joining aluminum alloys. This research significantly contributes to comprehending the energy absorption and toughness analysis of FSW butt joints in aluminum alloys, crucial for vehicle body technology applications.